1976
DOI: 10.1080/03014467600001671
|View full text |Cite
|
Sign up to set email alerts
|

New systems for dental maturity based on seven and four teeth

Abstract: An updated system for estimating dental maturity is presented. It extends the original system (Demirjian et al., 1973) based on radiographs of 7 teeth by including two extra stages, and by enlarging the standardizing sample to include 2407 boys and 2349 girls. Percentile standards from ages 2-5 to 17-0 years are presented separately for boys and girls. Scoring systems and percentile standards are presented for two different sets of 4 teeth and a comparison of all three systems is made. It is suggested that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
535
3
56

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 535 publications
(600 citation statements)
references
References 1 publication
6
535
3
56
Order By: Relevance
“…Terada et al 23) reported good fitting to the logistic curves in relation to the length of the finger bones and the mandible. Ever since Demirjian et al 18,19) reported a method for evaluation of the systemic growth stage on the basis of the fitting of the tooth development state to the logistic curve, numerous reports on the clinical application of this method have been published 24,25) . According to the reports on tooth development, including the reports by Nolla 16) and Moorrees et al 17) , inter-individual variations in tooth development are small, and tooth development shows close correlation with the calendar age in a stable manner.…”
Section: Fitting To the Logistic Curve And Comparison With Mean Growtmentioning
confidence: 99%
See 1 more Smart Citation
“…Terada et al 23) reported good fitting to the logistic curves in relation to the length of the finger bones and the mandible. Ever since Demirjian et al 18,19) reported a method for evaluation of the systemic growth stage on the basis of the fitting of the tooth development state to the logistic curve, numerous reports on the clinical application of this method have been published 24,25) . According to the reports on tooth development, including the reports by Nolla 16) and Moorrees et al 17) , inter-individual variations in tooth development are small, and tooth development shows close correlation with the calendar age in a stable manner.…”
Section: Fitting To the Logistic Curve And Comparison With Mean Growtmentioning
confidence: 99%
“…In these methods, the stages of crown and tooth root formation were scored on the basis of panoramic radiograph data. Demirjian et al 18,19) reported a method for evaluating the systemic growth stage by applying the development stage scores of seven teeth with assessed according to the method of Moorrees et al 17) to the logistic curve.…”
Section: Introductionmentioning
confidence: 99%
“…The method has the disadvantage that it does not include a valuation of the third molars, so can only be used for preadolescent ages. Subsequently the same author has produced updates to the original method, proposing a valuation system for four teeth (both premolars and molars) with different standards (Demirjian, 1976). In all cases, given that maturation development is different for the two sexes, the sex must be determined beforehand (Levesque et al, 1981).…”
Section: Dental Maturationmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13] On practical grounds, choice of the number of stages is a com promise between using a small number of stages that are eas ily identified and using a large number of stages that are less reliable. A more precise estimate of DA should be obtained by using a larger number of stages but, because of the diffi culty of identifying them reliably, the precision of the estimate will be reduced and the age assessment may be less accurate than if a smaller number of stages is used.…”
Section: Tooth Development Stagesmentioning
confidence: 99%